THE GEOMETRICAL SHAPE ON MEN’S KURTA DESIGN - Saipuddin Hasbullah; Wan Norliza Wan Bakar; Wan Junaidi Awang (Journal of Islamic, Social, Economics and Development, 2024)
Kurta is a loose-fitting collarless shirt or tunic worn in many regions of South Asia. Originated in India, the kurta has evolved stylistically over the countries, especially in South Asia, as a garment for everyday wear as formal occasion. As kurta catches the interest of many people, this paper is going to reveal a few geometrical shapes on men’s kurta design. The sole designer of UiTM has put into ideas different geometrical designs on men’s kurta. The shapes are arranged in tessellation to make up beautiful designs. This design can be analyzed through the lens of ethnomathematics comprising of observation, interview, and analysis. Future research can be made upon a few more insightful designs to attract local and foreign interests on kurta.